THE ROLE OF TRENDINESS IN STRENGTHENING THE RELATIONSHIP OF SOCIAL MEDIA MARKETING FEATURES WITH BRAND TRUST AND IT’S IMPACT ON PURCHASE DECISION - Azzahra Nur Aini (Universitas Islam Negeri Alauddin Makassar, 2024)
Some studies have investigated the impact of social media marketing features on purchasing decisions with Brand Trust as the mediation variable. But prior research indicates that brand trust merely acts as a mediator between informativeness and interaction when it comes to purchase decisions. The purpose of this study is to ascertain how Trendiness influences Purchasing Decisions in the skincare business by acting as a moderating variable between four marketing elements and Brand Trust. A self-administered survey with a scale of 1 to 10 is the research method employed. Purposive sampling was used to disseminate the questionnaire to 320 respondents. Structural Equation Modeling (SEM) with AMOS software is the analytical tool utilized. The results show that Interactivity, Informativeness, Entertainment and Perceived Relevance affect Brand Trust, Brand Trust affects Purchase Decisions and Trendiness can strengthen the relationship between Interactivity, Informativeness, Entertainment, and Perceived Relevance to Brand Trust. These results suggest the importance of brands adopting interactive, informative, entertaining, and relevant marketing strategies while staying current with trends to enhance Brand Trust.